Best practice in primary care pathology: review 7 - Smellie, W S A (BMJ Group, 2007)
This seventh best‐practice review examines four series of common primary care questions in laboratory medicine: (1) blood count abnormalities 2; (2) cardiac troponins; (3) high‐density lipoprotein cholesterol; and (4) viral diseases 2. The review is presented in a question–answer format, with authorship attributed for each question series. The recommendations are a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence‐based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. The recommendations are not standards, but form a guide to be set in the clinical context. Most are consensus based rather than evidence based. They will be updated periodically to take account of new information.